Collective leadership and safety cultures (Co-Lead): protocol for a mixed-methods pilot evaluation of the impact of a co-designed collective leadership intervention on team performance and safety culture in a hospital group in Ireland. Issue 11 (3rd November 2017) - McAuliffe, Eilish; De Brún, Aoife; Ward, Marie; O'Shea, Marie; Cunningham, Una; O'Donovan, Róisín; McGinley, Sinead; Fitzsimons, John; Corrigan, Siobhán; McDonald, Nick
Abstract : Introduction: There is accumulating evidence implicating the role of leadership in system failures that have resulted in a range of errors in healthcare, from misdiagnoses to failures to recognise and respond to patient deterioration. This has led to concerns about traditional hierarchical leadership structures and created an interest in the development of collective ways of working that distribute leadership roles and responsibilities across team members. Such collective leadership approaches have been associated with improved team performance and staff engagement. This research seeks to improve our understanding of collective leadership by addressing two specific issues: (1) Does collective leadership emerge organically (and in what forms) in a newly networked structure? and (2) Is it possible to design and implement collective leadership interventions that enable teams to collectively improve team performance and patient safety? Methods and analysis: The first phase will include a social network analysis, using an online survey and semistructured interviews at three time points over 12 months, to document the frequency of contact and collaboration between senior hospital management staff in a recently configured hospital group. This study will explore how the network of 11 hospitals is operating and will assess whether collective leadership emerges organically. Second, collective leadership interventions will be co-designed during a series of workshops with healthcare staff, researchers and patient representatives, and then implemented and evaluated with four healthcare teams within the hospital network. A mixed-methods evaluation will explore the impact of the intervention on team effectiveness and team performance indicators to assess whether the intervention is suitable for wider roll-out and evaluation across the hospital group. Ethics and dissemination: Favourable ethical opinion has been received from the University College Dublin Research Ethics Committee (HREC-LS-16–116397/LS-16-20). Results will be disseminated via publication in peer-reviewed journals, national and international conferences, and to relevant stakeholders and interest groups.